ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB), KESELAMATAN DAN KESEHATAN KERJA (K3) SERTA PENGARUHNYA TERHADAP KINERJA KARYAWAN PT. AIR MURING BENGKULU UTARA - Fauzan, Fauzan; Markoni, Markoni (Universitas Prof. Dr. Hazairin SH, 2022)
One of the mainstay commodities in Bengkulu Province is rubber plantation products. PT Air Muring Bengkulu Utara is a company engaged in rubber plantations and rubber processing in the form of crumb rubber with Ribbed Smoke Sheet (RSS) quality. This study aims to see the effect of the observed variables, namely Organizational Citizenship Behavior (X1) and Occupational Safety and Health (X2) on Employee Performance (Y) and test the hypotheses that have been formulated. This study uses quantitative data derived from distributing questionnaires to respondents and then processed in statistical analysis. The results of the analysis show that (1) Organizational Citizenship Behavior (X1) Occupational Safety and Health (X2) has a positive effect on Employee Performance (Y). (2) Occupational Safety and Health variables make a greater contribution than Organizational Citizenship Behavior to Employee Performance of PT Air Muring Bengkulu Utara. The implementation of this study shows that companies supported by employees who have good Organizational Citizenship Behavior, Occupational Safety and Health can develop their business